The Idle in 2 Thess 3.6–12: An Eschatological or a Social Problem? - Russell, R. (New Testament studies, 1988)
Much of the scholarly attention given the Thessalonian epistles has been devoted to various debates. These polemics have included the epistles' authenticity, with some arguing that 1 Thess 2. 13–16 and Thessalonians are post-Pauline, often by appealing to letter structure. Lack of agreement exists as well with the interpretation of Paul's eschatology–the letters' main concern - and difference of opinion also characterizes the function of Paul's apology in 1 Thess 2. 1–12 and his paraenesis, particularly in 1 Thess 4. 1–12. While scholars have actively pursued the pros and cons of these issues, most have been rather passive when it comes to discussing ‘the idle’ (l Thess 4. 11–12; 5. 14; 2 Thess 3. 6–13) – the second most significant theme in the epistles. They usually continue the traditional eschatological explanation for the origin of the problem. This study will survey the history of this interpretation, investigate 2 Thess 3. 6–13 and recommend that a social explanation best satisfies the evidence. This study also seeks to demonstrate the fallacy of explaining historical phenomena from just theological structures and the importance of the interaction between the world of ideas and social structures for interpretation – the importance of which has been shown by redaction criticism's concern for the Sitz im Leben and by recent social descriptions of early Christianity.